Efektivitas Pelatihan Positive Self-Talk dalam Meningkatkan Kepercayaan Diri Mahasiswa Baru Psikologi Universitas Pendidikan Indonesia - Agestianti, Ruth; Khalila Mustafid, Atha; Bulan Andari, Nafisya; Afifah Azzahra, Faza Tsalitsa; Ayu Regitha Pramesti, Ni Kadek; Zakariyya, Farhan; Lestari, Selfiyani (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
The demands and responsibilities in a new learning environment, namely college, can cause a crisis of confidence for students, especially new students. Positive self-talk is one alternative in increasing the confidence of new students. The purpose of this study was to determine the effectiveness of positive self-talk training in increasing the self-confidence of new psychology students at Universitas Pendidikan Indonesia. This study used a quantitative quasi-experimental method with a one group pretest-posttest design. The sample selection was determined using purposive sampling technique. Meanwhile, the subjects in this study amounted to 9 first semester students majoring in psychology at the University of Education Indonesia. Data analysis was carried out with the Wilcoxon test. The results showed a significance value of p = .042 (> 0.05), which means that positive self-talk is effective in increasing the confidence of new psychology students at Universitas Pendidikan Indonesia Keywords: Training; Positive Self Talk; College Students